Efficacy and safety of greater occipital nerve block for the treatment of cluster headache: a systematic review and meta-analysis. (1st November 2020) - Ornello, Raffaele; Lambru, Giorgio; Caponnetto, Valeria; Frattale, Ilaria; Di Felice, Chiara; Pistoia, Francesca; Sacco, Simona
ABSTRACT: Introduction: The treatment of cluster headache (CH) is challenging in view of the few evidence-based treatments. The authors aim to summarize the evidence of efficacy and safety of greater occipital nerve blocks (GONBs) in CH. Areas covered: The authors included papers indexed in PubMed and Web of Science from the beginning of indexing to 5 May 2020. They included both observational and randomized studies referring to patients with episodic and/or chronic CH. The authors identified 12 studies on 365 patients. Five studies (two randomized controlled trials) could be included in the meta-analyses. The pooled proportion of pain-free subjects at 1 month was 50% (95% CI 24–76%) with considerable heterogeneity (I 2 = 88%; P < 0.01). The pooled relative risk ratio of pain freedom at 1 month in active versus control groups in the two included randomized controlled trials was 4.86 (95% CI, 1.35–17.55) without statistical heterogeneity (I 2 = 0%; P = 0.39). Three studies showed decreased attack intensity, frequency, and duration after GONBs. The studies reported mild and transient adverse events. Expert opinion: Despite several limitations and considerable heterogeneity, the available data support the efficacy and safety of GONBs for the treatment of CH. Further large randomized trials are needed to confirm efficacy and establish optimal treatment protocols.